2017
DOI: 10.1038/s41598-017-11923-5
|View full text |Cite
|
Sign up to set email alerts
|

CHA2DS2-VASc score as predictor of ischemic stroke in patients undergoing coronary artery bypass grafting and percutaneous coronary intervention

Abstract: Ischemic stroke following coronary revascularization procedures remains one of the most potentially devastating complications. CHA2DS2-VASc score has been widely used for stroke risk stratification in AF patients. The aim of this nationwide study was to examine the association between the CHA2DS2-VASc score and ischemic stroke following coronary revascularization procedures. We identified patients undergoing coronary revascularization procedures, coronary artery bypass grafting (CABG) and percutaneous coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…The score of CHA2DS2-VASc was employed as a risk-measurement tool; it was recorded in treatment guidelines for stroke prevention and is a factor for predicting stroke. Tian et al suggest that CHA2DS2-VASc score should be on the clinical application [10]. This study demonstrated two significant findings: first, preoperative 1-year and perioperative variables are significant predictors.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The score of CHA2DS2-VASc was employed as a risk-measurement tool; it was recorded in treatment guidelines for stroke prevention and is a factor for predicting stroke. Tian et al suggest that CHA2DS2-VASc score should be on the clinical application [10]. This study demonstrated two significant findings: first, preoperative 1-year and perioperative variables are significant predictors.…”
Section: Discussionsupporting
confidence: 50%
“…In this research, the baseline characteristic variables were sex, Charlson comorbidity index (CCI) score, number of anastomosis vessels, and patient comorbidities (Supplementary Materials) including: hypertension, hyperlipidemia, diabetes mellitus (DM), congestive heart failure (CHF), peripheral vascular disease (PVD), coronary artery disease (CAD), chronic obstructive pulmonary disease (COPD), myocardial infarction (M), chronic kidney disease (CKD), end-stage renal disease (ESRD), and stroke. Blood transfusion (94001C, 94002C, 4013C, 94015C, 94003C), mechanical ventilation (57001B, 57002B, 57003B) in the preoperative one year, and CHA2DS2-VASc score [10,11] were also included. CHA2DS2-VAS was calculated for each research patient using a history of hypertension, diabetes mellitus, congestive heart failure, and vascular disease.…”
Section: Comorbidities and Variable Definitionsmentioning
confidence: 99%
“…including advanced age, aortic calcification, renal failure, and diabetes have all been identified to account for the early and delayed incidence of postoperative stroke. [6][7][8] Over several decades, we have witnessed significant technical and technological advancements in the context of CABG. These include routine use of preoperative and intraoperative advanced imaging platforms, improvements in surgical technique, and optimisation of cardiopulmonary bypass systems.…”
mentioning
confidence: 99%
“…The baseline characteristic variables in this study included sex (male/female), age, Charlson comorbidity index (CCI), and CHA2DS2-VAS scores [10,11]. Each patient's comorbidities could be traced to the date before the CABG surgery (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013).…”
Section: Comorbidities and Risk Factorsmentioning
confidence: 99%